A study on consumer’s impulse buying behavior decision: live streaming shopping on crossborder e platform - Leong, Jing Ying (2022)
With the rapid growth of the Internet economy and the emergence of e-commerce platforms in recent years, merchandise sales via live streaming commerce have also become widespread. This paper aimed to study the influencing factors of impulse buying decision on live streaming shopping. Through this study, it helped sellers in digital transformation and set as a benchmark for the local seller and marketers to study. Based on theoretical research, this study focusses on factors such as price promotion, promotion time limit, perceived opportunity cost, consumer-streamer interaction, consumer-consumer interaction, visual appeal, impulse buying decision, as well as perceived risk which act as a mediator based on the Stimulus-Organism-Response (SO-R) model. 254 sets of questionnaires had been collected and analyse through the Statistical Package for Social Science (SPSS). Based on the result, it showed that price promotion, promotion time limit, and perceived opportunity cost have significant effect toward the consumers’ impulse buying decision while consumer-streamer interaction, consumer-consumer interaction, and visual appeal have insignificant effect. Meanwhile, perceived risk only had mediation effect between price promotion, promotion time limit, and perceived opportunity cost and impulse buying decision. Nevertheless, it did not play a mediating role between consumer-streamer interaction, consumer-consumer interaction, and visual appeal and impulse buying decision. The finding suggested some marketing strategy for sellers which includes establish of suitable pricing promotion techniques and variety of techniques to lower the level of perceived risk of consumers.